Pharmacovigilance and reporting oversight in US FDA fast-track process: bisphosphonates and osteonecrosis of the jaw - Edwards, B.J.; Gounder, M.; McKoy, J.M.; Boyd, I.; Farrugia, M.; Migliorati, C.; Marx, R.; Ruggiero, S.; Dimopoulos, M.; Raisch, D.W.; Singhal, S.; Carson, K.; et al. (The Lancet Oncology, 2008)
More than half of all serious adverse reactions are identified 7 or more years after a drug receives approval from the US Food and Drug Administration (FDA). In 2002, 9 months after the intravenous bisphosphonate zoledronic acid received regulatory approval for marketing, the FDA received reports of nine patients with cancer, who were treated with zoledronic acid, who unexpectedly developed osteonecrosis of the jaw. During the next 2 years, three oral surgeons described 104 patients with cancer with osteonecrosis of the jaw in the medical literature and identified intravenous bisphosphonate therapy as being common to the care of these patients. In subspecialty medical, radiology, and dental journals, case reports and case series described clinical features of osteonecrosis of the jaw in patients with cancer who were treated with bisphosphonates. Manufacturer-sponsored epidemiological studies reported the first estimates of the incidence of this toxic effect, ranging from 0·1% to 1·8%. By contrast, independent epidemiological efforts from clinicians and the International Myeloma Foundation reported incidence estimates between 5% and 10%. Between 2003 and 2005, warnings about the risks of bisphosphonate-associated osteonecrosis were disseminated by national regulatory agencies, the manufacturers of bisphosphonates, and the International Myeloma Foundation. From 2006, independent clinical recommendations for diagnosis, prevention, and treatment of this toxic effect have been disseminated by manufacturers, national regulatory authorities, the International Myeloma Foundation, and medical specialty organisations. Furthermore, independent efforts by pharmaceutical manufacturers, dental and medical professionals, a non-profit organisation (the International Myeloma Foundation), patients, and regulatory authorities has led to the rapid identification and dissemination of safety information for this serious adverse reaction. Better coordination of safety-related pharmacovigilance initiatives is now needed. © 2008 Elsevier Ltd. All rights reserved.